Genome-Wide Identification, Expression Profiling, and Functional Validation of Oleosin Gene Family in Carthamus tinctorius L. - Lu, Yubin; Chi, Menghan; Li, Lixia; Li, Haoyang; Noman, Muhammad; Yang, Ying; Ji, Kun; Lan, Xinxin; Qiang, Weidong; Du, Linna; Li, Haiyan; Yang, Jing (Frontiers in Plant Science, 2018)
Carthamus tinctorius L., commonly known as safflower, is an important oilseed crop containing oil bodies. Oil bodies are intracellular organelles in plant cells for storing triacylglycerols (TAGs) and sterol esters. Oleosins are the most important surface proteins of the oil bodies. We predicted and retrieved the sequences of eight putative C. tinctorius oleosin (Ctoleosin) genes from the genome database of safflower. The bioinformatics analyses revealed the size of their open reading frames ranging from 414 to 675 bp, encoding 137 to 224 aa polypeptides with predicted molecular weights of 14.812 to 22.155 kDa, all containing the typical “proline knot” motif. Reverse transcription quantitative polymerase chain reaction (RT-qPCR) determined the spatiotemporal expression pattern of Ctoleosin genes, which gradually increased and peaked during flowering and seed ripening, and decreased thereafter. To validate their role in plant development, we transformed and overexpressed these eight putative Ctoleosin genes in Arabidopsis. Overexpressing Ctoleosins did not affect leaf size, although silique length was altered. Arabidopsis transformed with Ctoleosin3, 4, and 5 grew longer siliques than did the wild-type plants, without altering seed quantity. The 100-grain weight of the transgenic Arabidopsis seeds was slightly more than that of the wild-type seeds. The seed germination rates of the plants overexpressing Ctoleosin4 and 6 were slightly lower as compared with that of the wild-type Arabidopsis, whereas that in the other transgenic lines were higher than that in the wild-type plants. The overexpression of Ctoleosin genes elevated the oil content in the seeds of transgenic Arabidopsis. Our findings not only provide an approach for increasing the oil content, but also for elucidating the intricate mechanisms of oil body synthesis.